Patterns of care and outcomes among triple‐negative early breast cancer patients in South Western Sydney. Issue 5 (2nd May 2018) - Naher, Sayeda; Tognela, Annette; Moylan, Eugene; Adams, Diana H.; Kiely, Belinda E
Abstract: Background: Triple‐negative breast cancer (TNBC) represents 12‐24% of all breast cancer and carries a poor prognosis upon recurrence. Little is known of the treatment, or timing and frequency of recurrences outside of a clinical trial. Aim: We describe the patterns of care and outcomes of women with TNBC treated at two cancer centres in Sydney, NSW, Australia, to help oncologists talk to women with this subtype of breast cancer about their likely prognosis. Methods: We searched the electronic medical record for women with stages I–III TNBC diagnosed from 2006 to 2014. For each woman, we recorded demographics, tumour characteristics, treatment details, recurrences and survival using the Kaplan–Meier method. Results: We identified 137 women with a median age of 55 years (interquartile range (IQR) 44–63). The median tumour size was 25 mm (IQR 16–35). Most women had grade 3 (92%) and ductal carcinomas (89%), and 35% were node positive; 113 (82%) patients received (neo)adjuvant chemotherapy. The most prescribed regimens for node‐negative tumours were: fluorouracil, epirubicin and cyclophosphamide (FEC) × 6 (23pts, 35%), and for node‐positive tumours, FEC‐Docetaxel (18pts, 40%). Adjuvant radiotherapy was delivered to 114 (83%) patients. After a median follow up of 40 months, 17 patients (12%) had a recurrence. All but one recurrence (94%) occurred within 3 years of diagnosis. Twelve women received palliative chemotherapy, and 14 women have died. The median survival from the time of recurrence was 18 months (IQR 5–26). Seven women (5%) had a documented BRCA1 mutation, and four women (3%) had a documented BRCA2 mutation. Conclusions: TNBC affects women at a relatively young age and tends to recur early. Survival following metastatic disease is short, and more effective therapies are needed.